(untitled) (International Journal of Physiotherapy, 2023)
Background: Spasticity in patients who survived after stroke is due to various mechanisms, in which the pathophysiology is widely varying. The results may be promising if there is a possibility of setting a framework for selecting appropriate treatment options based on impaired mechanisms. So, there is a need to review the literature available on electrical stimulation techniques for managing spasticity after stroke. Methods: 16 articles were included in this systematic review through electronic databases, including Pubmed, Google Scholar, Cochrane, library, Elsevier, Research Gate, and Science Direct, published between 2005 to 2022, which studied the effects of electrical stimulation on spasticity in hemiplegic patients as one of the interventions. Review articles, case studies, and studies with poor methodology were excluded from the review. Results: Reductions in Spasticity and improvements in range of motion were noted with the application of NMES combined with other interventions. On sensitivity analysis related to the site of application of NMES, wrists showed no effects on both Spasticity and ROM, and elbows showed no effects on spasticity. When a range of motion is considered one of the outcome measures, the results supported the effects of NMES, and for other outcomes, the results did not confirm the effects of NMES. Conclusion: 16 randomized controlled trial articles were reviewed, and positive effects of electrical stimulation on spasticity management were reported. Most of them reported recovery in plantar flexor spasticity. There is a scope for research on upper limb muscle spasticity and neurophysiological aspects of recovery that help in functional recovery.